A structural approach of the AI social representations. Robot humanizing technology? - Gerakopoulou, Patricia; Christakis, Nikolas (Psychology: the Journal of the Hellenic Psychological Society, 2025)
Strongly related to a “technological mythology” referred to Promethean promises and threats, Artificial Intelligence draws increasingly impressive attention from the media, as well as from the lay public. The purpose of this research paper is to investigate the content and structure of the AI social representations of undergraduate students from all six Media and Communication University departments in Greece (N=249) relying on original qualitative data collected using a “free association” questionnaire consisting of two open questions. In question one, participants were asked to write three to five words that first come to mind when they think of the term “Artificial Intelligence”. In the second question, they were asked to describe further each of their previous answers. The data generated fell under six major thematic categories: Technology, Future, Threats, Uses, Robot, and Human (characteristics). These categories were further analyzed according to frequency and rank to produce the “square of the AI social representation”, which is consisted of the central system (Technology & Future), the peripheral system (Threats & Uses) and the “grey area” (Robot & Human). The interpretation and discussion of the results lead to the main conclusion that the representation element of the Robot represents the ideal blurring of the boundaries between Human and AI (the latter far superior in “intelligence”, e.g. data processing), attributing more familiar “human” characteristics to the, otherwise, vague and ambiguously perceived (Threats and Uses) technological object.